2021
DOI: 10.1002/ags3.12497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of creating a jejunal pouch on postoperative quality of life after total gastrectomy: A cross‐sectional study

Abstract: Aim Total gastrectomy results in the complete loss of gastric function and the development of severe postgastrectomy syndrome. During the jejunal pouch procedure following total gastrectomies, a substitute stomach is created to alleviate the effects of postgastrectomy syndrome. However, the procedure's effectiveness remains controversial. This study aimed to explore the effect of jejunal pouch creation after total gastrectomy on postoperative quality of life. Methods A nationwide multi‐institutional cross‐sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Postoperative QOL in PG [ 10 11 12 ], SRDG [ 13 14 15 ], and TGJP [ 16 17 18 19 ] have been reported to be higher than in TG. Based on this study, the PGSAS NEXT study found that postoperative QOL was better with PG [ 29 ], SRDG [ 30 ], and TGJP [ 31 ] than with TG, even after adjusting for the effects of various confounders using multiple regression analysis, supporting a previous report. However, no study has simultaneously compared these procedures for proximal gastric cancer to determine the severity and characteristics of their impact on postoperative QOL.…”
Section: Discussionsupporting
confidence: 85%
“…Postoperative QOL in PG [ 10 11 12 ], SRDG [ 13 14 15 ], and TGJP [ 16 17 18 19 ] have been reported to be higher than in TG. Based on this study, the PGSAS NEXT study found that postoperative QOL was better with PG [ 29 ], SRDG [ 30 ], and TGJP [ 31 ] than with TG, even after adjusting for the effects of various confounders using multiple regression analysis, supporting a previous report. However, no study has simultaneously compared these procedures for proximal gastric cancer to determine the severity and characteristics of their impact on postoperative QOL.…”
Section: Discussionsupporting
confidence: 85%
“…Both methods often use a linear stapler to add to the reconstruction. There is no fixed definition of pouch size or method for creating the pouch; however, in practice, a more convenient aboral pouch is likely to be preferred 8,11,18) .…”
Section: Aboral Pouchmentioning
confidence: 99%
“…Weight loss after total gastrectomy occurs in approximately 10-15% of cases. Decreased food intake and esophageal reflux symptoms due to bile reflux are particularly well-known causes [5][6][7][8] . Several reconstructive innovations reportedly improve PGS and QOL postoperatively in patients who have undergone total gastrectomy procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations